THE ANALIZE OF WASTE ELIMINATION ON SA CONTACT BLOCK TO INCREASED THE OUTPUT BY LEAN MANUFACTURING METHOD (STUDI CASE: PT SCHNEIDER ELECTRIC) - Merjani, Abdullah; Afriantika, Nadila (SIGMA TEKNIKA, 2024)
PT. Schneider Electric Manufacturing is a global company leading digital transformation in the fields of energy management and automation. PT. Schneider its prioritizes continuous improvement to control the production process. These include modular and Monoblock sub-assemblies. In controlling effectiveness in a production system it should be a good level on utility (utilization), but after analysed it found low utilization on line production Monoblock many problems with waste from production operators, material transfer and waiting times due to unbalanced processes resulting in less output. (not reaching the target) this has a huge impact on efficiency and productivity. To increase output and utility, use 3 lean manufacturing methods, including Kaizen, Line balancing and Kanban super market to improve overcome problems in the production area. After implementation, utility and output become better.